Analysis of Batik Business Development Strategy in Kliwonan Batik Tourist Village, Masaran District, Sragen District - Putri, Windy Mahardhika; Suranto, S (Proceedings International Conference on Education Innovation and Social Science, 2023)
This study aims to describe the development strategy used by batik businesses in the Kliwonan Batik Tourism Village, Masaran District, Sragen Regency. This type of research is qualitative with a case study design. The object of research is the strategy of developing a batik business and the subjects in this study are batik business owners, batik business actors, and industrial and trade extension workers in the Kliwonan Batik Tourism Village, Masaran District, Sragen Regency. Data collection is done by interviews, observation and documentation. The validity of the data using source triangulation analysis and method triangulation. The analysis technique uses data collection, data reduction and data presentation. The results showed that the development strategy used by the batik business in Kliwonan Batik Tourism Village, Masaran District, Sragen Regency included factors of internal strategy and external strategy. The results of the SWOT analysis of alternative strategies for developing one's own business, maintaining product quality and product variety according to people's purchasing power, developing product variations according to customer demand, product innovation thereby increasing the variety of products presented to customers, improving service to customers, fostering good relations with customers, collaborating with batik traders, promoting through online media or social media as well as offering group products and adding distribution channels such as agents and resellers.